STRATEGI ANTISIPASI POTENSI BENCANA ALAM DI KABUPATEN BANDUNG (Institut Pemerintahan Dalam Negeri, 2021)
This research is motivated by the high level of vulnerability and potential for natural disasters in Bandung district and needs to be anticipated through strategies, both policy and practical strategies related to disaster management. This research is a descriptive qualitative research using several theoretical approaches including the theory of policy strategy and disaster management as well as other theories that are considered relevant. The results of the study show that there is a form of Government commitment in disaster management efforts carried out by BNPB at the national level and BPBD at the regional level. Strategies that can be carried out can be analyzed from the policy aspect where there are several policy strategies that have been carried out by the Bandung Regency Government in anticipating natural disaster vulnerability. 2 of 2013 concerning the Implementation of Disaster Management and at a practical level, disaster management has been carried out in a planned and systematic manner.Keywords: Strategy, Potential Natural Disasters; Disaster management